Institutional Logics in Child Rearing: A Case Study of Cha-am District, Phetchaburi Province - Khotsing, Thannaphat; Ratnatilaka Na Bhuket, Phichai; Bhanthumnavin, Duchduen (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The objectives of this research were: 1) to study the relationship between family determinants and child development, 2) to examine the field of child rearing, and 3) to investigate and analyze the sets of institutional logics found in the child-rearing field relating to developmental delay. The methodology is mixed-method research by applying qualitative and quantitative research. The samples of quantitative research were 396 caregivers of children. The quantitative analysis included frequency, percent, Chi-Square Test, Logistic Regression, and Discriminant Analysis. The target groups of qualitative research were 18 families of children with developmental delays. The qualitative analysis included content analysis and causal analysis by using Mill’s Methods. It was found that 33.3% of the sample experienced developmental delays. The factors related to child development including 1) main caretaker’s income, 2) employment status of the main caretaker, 3) the number of children in a family, 4) the number of the main caretaker, the relation between children and the main caretakers, and elderly relative in the family. According to the institutional logics relating to the children with developmental delays, results show that the community logic, market logic, and family logic associate with developmental delays in children. In contrast, professional logic associates with normal development in children. The public health organization may have to carry out the project about changing the attitudes of parents include 1) not allowing children to play on a smartphone too long, 2) training for children to help themselves, and 3) controlling children behaviors according to the situation.